Gitelman Syndrome in a School Boy Who Presented with Generalized Convulsion and Had a R642H/R642W Mutation in the SLC12A3 Gene. (15th July 2014) - Makino, Shigeru; Tajima, Toshihiro; Shinozuka, Jun; Ikumi, Aki; Awaguni, Hitoshi; Tanaka, Shin-ichiro; Maruyama, Rikken; Imashuku, Shinsaku
Abstract : An 8-year-old Japanese boy presented with a generalized convulsion. He had hypokalemia (serum K 2.4 mEq/L), hypomagnesemia, and metabolic alkalosis (BE 5.7 mmol/L). In addition, his plasma renin activity was elevated. He was tentatively diagnosed with epilepsy on the basis of the electroencephalogram findings and was treated by potassium L-aspartate and carbamazepine to control the hypokalemia and seizure, respectively. However, a year later, the patient continued to have similar abnormal laboratory data. A presumptive diagnosis of Gitelman syndrome (GS) was then made and the patient's peripheral blood mononuclear cells were subjected to sequence analysis of the SLC12A3 gene, which encodes a thiazide-sensitive sodium-chloride cotransporter. The patient was found to have compound heterozygous mutations, namely, R642H inherited from his father and R642W inherited from his mother. Thus, if a patient shows persistent hypokalemia and metabolic alkalosis, GS must be considered, even if the patient exhibits atypical clinical symptoms.